Bankruptcy: is it enough to forgive or must we also forget? - Ronel Elul; Piero Gottardi (Center for Economic Studies and ifo Institute (CESifo), 2008)
In many countries, lenders are not permitted to use information about past defaults after a specified period of time has elapsed. We model this provision and determine conditions under which it is optimal. We develop a model in which entrepreneurs must repeatedly seek external funds to finance a sequence of risky projects under conditions of both adverse selection and moral hazard. Forgetting a default typically makes incentives worse, ex-ante, because it reduces the punishment for failure. However, following a default it may be good to forget, because by improving an entrepreneur's reputation, forgetting increases the incentive to exert effort to preserve this reputation. Our key result is that if (i) borrowers' incentives are sufficiently strong, (ii) their average quality is not too low, (iii) the output loss from low effort is not too large, and (iv) agents are sufficiently patient, then the optimal law would prescribe some amount of forgetting that is, it would not permit lenders to fully utilize past information. We also argue that forgetting must be the outcome of a regulatory intervention by the government no lender would willingly agree to ignore information available to him. Finally, we show that the predictions of our model are consistent with the cross-country relationship between credit bureau reporting regulations and the provision of credit, as well as Musto (2004)'s evidence on the impact of these regulations on individual borrower and lender behavior.
Keywords: D86; G33; K35; 330; tax competition; trade unions; foreign direct investment; Konkurs; Zeit; Unternehmensgründung; Finanzierung; Adverse Selection; Moral Hazard; Unternehmer; Ökonomischer Anreiz; Theorie